Experiments with methods to reduce attrition in longitudinal surveys - Laura Fumagalli; Heather Laurie; Peter Lynn (University of Essex, Institute for Social and Economic Research (ISER), 2010)
We conduct two large-scale randomised experiments on the British Household Panel Survey (BHPS) to study methods of reducing panel attrition. The first experiment compares different strategies for tracing and maintaining contact with sample members. We find that change-of-address cards conditional on moving are most effective both in increasing response rates and in reducing fieldwork costs. The second experiment substitutes the standard between-wave Respondent Report with reports tailored for specific categories of respondents. We find that tailored reports have a positive though small effect on the number of young people completing a face-to-face interview and increase cooperation for busy people when telephone interviews are included.
Keywords: C81; C83; C90; 330; attrition; non-response; tailoring; respondent incentives; longitudinal surveys; experiments; Befragung; Meinungsforschung; Wissenschaftliche Methode; Großbritannien